Exploring long-term variability of Nephrops norvegicus population in the Porcupine Bank (SW Ireland) - González-Herraiz, Isabel; Torres, María de los Ángeles; Fariña-Pérez, Celso (2007)
Presentation Nephrops norvegicus is a commercial species of the bottom fisheries in European western waters which yield has long-term variability. Their distribution is linked to suitable habitats of muddy sediment in which adults construct burrows but the influence of environmental factors on the populations was poorly investigated. Variability in the catch per unit effort (CPUE) of Nephrops norvegicus from Porcupine Bank (Southwest of Ireland) was explored using a time series approach. The CPUE time series (1979-2005) exhibited a seasonal pattern. The seasonal decomposition of the CPUE shows a declining trend in the trend and cycle component from 1982 onwards. ARMA univariate and dynamic regression models were fitted to the CPUE time series. Population (proportion of males, proportion of ovigerous females and recruits) and North Atlantic Oscillation index were tested at different lags to investigate possible factors related to the yield fluctuations.